Pengaruh yoga terhadap Nyeri Sendi pada Lansia di PSLU Blitar - Ning Arti Wulandari (STIKes Patria Husada Blitar, 2016)
The aging process is a process of gradual disappearance of the network’s ability to repair itself and maintain its normal functions. Some physical changes will occur on all systems, for example in the musculoskeletal system decreased fluid in the bone resulting in joint stiffness and joint pain. The management of joint pain with some nonpharmacological therapy one of them is yoga. The purpose of this study was to identify the effectiveness of yoga to the joint pain of elderly. Method; This study design used pre and post test without control, with the number of sample 10 elderly people by purposive sampling. This research was conducted in elderly social services Blitar 11 to 14 December 2016. The data collected by using the Visual Analog Scale (VAS). The results of this study before the elderly did yoga was 80% felt joint pain scale was after attending a yoga 50% of elderly felt mild pain, the results of statistical analysis with Paired T Test was p = 0.001 means that there was an effect on joint pain by yoga exercises. Therefore, health employee could facilitate the elderly to follow yoga by bringing yoga instructors since yoga is considering not only reduces joint pain but also reduce stress and improve the energy balance.